Simultaneously Inhibiting Lithium Dendrites Growth and Polysulfides Shuttle by a Flexible MOF‐Based Membrane in Li–S Batteries. Issue 34 (14th October 2018) - He, Yibo; Chang, Zhi; Wu, Shichao; Qiao, Yu; Bai, Songyan; Jiang, Kezhu; He, Ping; Zhou, Haoshen
Abstract: Lithium–sulfur (Li–S) batteries are considered a promising candidate for next‐generation energy storage devices due to their ultrahigh theoretical energy density (≈2600 Wh kg −1 ). However, the uncontrolled growth of Li dendrites and the adverse effect of polysulfide shuttling seriously hinder their practical applications. Herein, a metal organic framework based membrane (MOF@PVDF‐HFP) with good flexibility is designed and fabricated by a facial vacuum filtration strategy. The highly uniform pore sizes of MOF particles facilitate homogenous Li‐ion fluxes, fundamentally inhibiting the growth of Li dendrites and resulting in stable Li plating/striping even at a quite high current density (10 mA cm −2 ). In addition, owing to the narrow pore size window of MOF nanoparticles, the MOF@PVDF‐HFP membrane serves as an effective barrier for suppressing the polysulfide shuttle, realizing an ultralong cycle life Li–S coin cell with an ultralow capacity fading upon 2000 cycles (0.015% per cycle). Moreover, high specific capacity (1269 mA h g −1 ) and excellent capacity retention (936 mA h g −1 after 200 cycles) of a flexible Li–S pouch cell with a high sulfur loading (5.8 mg cm −2 ) demonstrate the potential of MOF@PVDF‐HFP membranes for the development of practical energy storage devices. Abstract : Li dendrites and polysulfides shuttles result in the short cycle life of Li–S batteries. A MOF@PVDF‐HFP membrane with highly uniform pore sizes facilitates homogenous Li‐ion fluxes, fundamentally inhibiting the growth of Li dendrites. In addition, owing to the narrow pore size window, the MOF@PVDF‐HFP membrane serves as an effective barrier for suppressing the polysulfides shuttle, realizing long cycle life for both Li–S coin and pouch cells.